Local management and governance improve natural resource incomes of communal conservancies in Namibia - J. D. Goergen; M. P. Louis; K. F. Kellner; G. J. Roloff; M. Lindeque; J. L. Belant (Conservation Science and Practice)
Abstract Effective governance of communal institutions is critical to financial sustainability of community‐based natural resource management economies. We evaluated effects of local management and governance on income earned by communal conservancies in Namibia during 2011–2022. We compiled annual income and performance scores for natural resource management and institutional governance using conservancy accounting and ‘event book’ monitoring data (governance performance collected since 2019). Conservancies earning >$0 income generated a median annual $60,518 since 2011 and $50,283 since 2019 (17% less than during 2011–2022), which reflected a decline in tourism during the COVID‐19 pandemic despite an increase in grants received. Income increased with years since conservancy establishment, higher management performance, presence of nongovernmental organization (NGO) support within conservancies, and annual general meeting (AGM) occurrence. Higher management performance positively affected the probability conservancies earned >$0 since 2011 and 2019. Income earned during 2019–2022 also increased with higher governance performance. Median management and governance performances across conservancies were only about 50% of their maximum scores, indicating higher income potential with improved performance. Support from NGOs remained critical to financial sustainability of conservancies and AGMs were important governance functions. Natural resource management and institutional governance facilitated income generation by Namibia's conservancies, but more emphasis on benefit distribution could increase socioeconomic impact. We recommend that Namibia's conservancies, particularly those established more recently or without NGO presence, prioritize improving local management and governance to develop more sustainable community‐based natural resource economies.